Offset Credits in the EU Emissions Trading System : A Firm-Level Evaluation of Transaction Costs - Helene Naegele (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
International offset certificates have systematically traded at a lower price than European Union Allowances (EUAs), although they are perfect substitutes. Firms therefore had a strong incentive to use the cheaper certificates up to the maximum quantity fixed by the regulator. This study highlights that a considerable number of firms did not use their offset credit entitlement and by doing so seemingly forwent profits, which supports the idea that significant transaction costs exist in carbon permit trade. While most of the literature on emission trading evaluates the efficiency of regulation in a frictionless world, firms in reality face managerial costs of compliance with regulation. This study examines the use of international offset credits within the EU Emissions Trading System (EU ETS) for carbon dioxide, in order to assess the relevance of such managerial and information-related transaction costs. This study further establishes a model of firm decision under fixed entry costs and estimates the size of transaction costs rationalizing firm behavior using both standard parametric and semi-parametric binary quantile regression methods. These costs appear to be sizable and make active optimization of compliance unprofitable for many small emitters. It appears that a large portion of these transaction costs stems from participation in the EU ETS in general, rather than additional participation in the offset trade.
Keywords: Q58; H23; D23; 330